Messianic mystics - Idel, Moshe, 1947- (Yale University Press, 1998)
"One of the worl'ds leading scholars of Jewish thought examines the long tradition of Jewish messianism and mystical experience."
Keywords: Messiah -- Judaism -- History of doctrines.; Cabala -- History.; Messie -- Judaïsme -- Histoire des doctrines.; Kabbale -- Histoire.; RELIGION -- Judaism -- Theology.; Cabala; Messiah -- Judaism -- History of doctrines; History